Constraining central Neo‐Tethys Ocean reconstructions with mantle convection models. Issue 18 (29th September 2016) - Nerlich, Rainer; Colli, Lorenzo; Ghelichkhan, Siavash; Schuberth, Bernhard; Bunge, Hans‐Peter
Abstract: A striking feature of the Indian Ocean is a distinct geoid low south of India, pointing to a regionally anomalous mantle density structure. Equally prominent are rapid plate convergence rate variations between India and SE Asia, particularly in Late Cretaceous/Paleocene times. Both observations are linked to the central Neo‐Tethys Ocean subduction history, for which competing scenarios have been proposed. Here we evaluate three alternative reconstructions by assimilating their associated time‐dependent velocity fields in global high‐resolution geodynamic Earth models, allowing us to predict the resulting seismic mantle heterogeneity and geoid signal. Our analysis reveals that a geoid low similar to the one observed develops naturally when a long‐lived back‐arc basin south of Eurasia's paleomargin is assumed. A quantitative comparison to seismic tomography further supports this model. In contrast, reconstructions assuming a single northward dipping subduction zone along Eurasia's margin or models incorporating a temporary southward dipping intraoceanic subduction zone cannot sufficiently reproduce geoid and seismic observations. Key Points: Geodynamic modeling results provide evidence for the former existence of large back‐arc basins in the Neo‐Tethys Comparisons to seismic tomography and the geoid show that standard reconstructions with purely northward dipping subduction are outdated The speed up of the Indian Plate at 65 Ma may be due to a combination of a coupled double subduction zone system and plume push